2016
DOI: 10.1179/1351000215y.0000000029
|View full text |Cite
|
Sign up to set email alerts
|

LINE-1 methylation levels, a biomarker of weight loss in obese subjects, are influenced by dietary antioxidant capacity

Abstract: www.clinicaltrials.gov : NCT01087086.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
(39 reference statements)
2
23
0
Order By: Relevance
“…The main finding of this research is that the DNA methylation levels of three selected CpG sites located in miRNA coding regions (miR‐1203, miR‐412 and miR‐216A) were associated with obesity in children. These results confirm that peripheral blood samples may be used as a surrogate source of DNA and miRNA in epigenetic biomarker research, as other studies have previously shown .…”
Section: Discussionsupporting
confidence: 91%
“…The main finding of this research is that the DNA methylation levels of three selected CpG sites located in miRNA coding regions (miR‐1203, miR‐412 and miR‐216A) were associated with obesity in children. These results confirm that peripheral blood samples may be used as a surrogate source of DNA and miRNA in epigenetic biomarker research, as other studies have previously shown .…”
Section: Discussionsupporting
confidence: 91%
“…Several polymerase chain reaction (PCR)-based methods have been used in order to easily analyze DNA methylation from leukocytes. In this context, global DNA methylation has been assessed measuring the methylation of CpG islands in the promoter region of the long interspersed nucleotide element 1 ( LINE1 ) retrotransposon [30,31,32,33], the only active, autonomous transposable element in humans [34]. Besides, some studies have investigated the relation between methylation pattern of genes with obesity, metabolic disturbances, and aging [27,28,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these alterations include DNA methylation ( 83 , 84 ) and histone modifications ( 85 , 86 ), which are associated with factors such as diet ( 87 ), stress ( 88 ) and other modifiable lifestyles, including smoking ( 89 ) and alcohol consumption ( 90 ). Global DNA methylation levels, measured in PBMCs with Long Interspersed Nucleotide Elements-1 (LINE)-1 as a surrogate endpoint, was reported to be significantly higher in participants with a higher degree of weight loss compared with those who exhibited low responses (<8%) to energy-restricted treatment ( 91 ). LINE-1 was reported to be positively associated with healthy energy and micronutrient intake, and inversely associated with body fat mass ( 92 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global and gene-specific DNA methylation alterations, which vary with age, sex and socioeconomic status, may also be predictive biomarkers of weight loss response to intervention programs ( 91 ). Global DNA methylation and inflammatory gene promoter hypermethylation are reported to be early biomarkers of adiposity and metabolic alterations ( 93 ).…”
Section: Discussionmentioning
confidence: 99%